ASPEK KESELAMATAN OPERASI PENYIMPANAN SEMENTARA BAHAN BAKAR NUKLIR BEKAS - Ahmad Indra Permana (Jurnal Teknik Lingkungan, 2013)
AbstractFacility of Instalation Storage for Spent Fuel (ISFSF) designed to be able to place Spent Nuclear Fuel (SNF) as result of 25 years Versatile Reactor – G. A. Siwabbesy added by 1 core unload. In normal operation, there is change of 8 SNF and there is 7 cycles in a year with storage capacity is 1448 SNF elements including used element control rod.  Until the end of 2011, real situation of ISFSF has only 245 SNF and normal operation has 6 times change SNF each cycles and 4 cycles in a year, therefore storage capaccity of ISFSF can reach 60 operational years. After SNF moved from reactor fuel to ISFSF emits heat 42,10 watt each elements and heat total is 6 kW. ISFSF completed with cooler system to hold on water temperation not more than 35 ºC and VAC hold on air temperation not more than 25 ºC. Heat transfer in ISFSF shows the increasing 0,057 ºC of water temperature each day in non operational cooler system and VAC operates into 67 ºC abnormal temperature limit for 560 days. While in non opeartional cooler system condition and VAC, there is increasing 0,25 ºC each day for water temperature with the achievement limitation 128 days and the air temperature becomes 35 ºC each day in 2 hours 11 minutes. Value of radiation exposure in ISFSF between 0,14 – 0,77 μSv each hour is safe for workers and the environment. While surface contamination value of alpha from 0.00 to 0.00 Bq/cm2, beta from 0.00 to 0.02 Bq/cm2 and air contamination alpha values from 0.00 to 0.00 Bq/cm2, beta from 0,00 to 0.23 Bq/cm2, included into the low contamination areas and is still below the level of contamination.